In-depth characterization of self-healing polymers based on π–π interactions - Meurer, Josefine; Hniopek, Julian; Ahner, Johannes; Schmitt, Michael; Popp, Jürgen; Zechel, Stefan; Peneva, Kalina; Hager, Martin D. (Beilstein Journal of Organic Chemistry, 2021)
The self-healing behavior of two supramolecular polymers based on π–π-interactions featuring different polymer backbones is presented. For this purpose, these polymers were synthesized utilizing a polycondensation of a perylene tetracarboxylic dianhydride with polyether-based diamines and the resulting materials were investigated using various analytical techniques. Thus, the molecular structure of the polymers could be correlated with the ability for self-healing. Moreover, the mechanical behavior was studied using rheology. The activation of the supramolecular interactions results in a breaking of these noncovalent bonds, which was investigated using IR spectroscopy, leading to a sufficient increase in mobility and, finally, a healing of the mechanical damage. This scratch-healing behavior was also quantified in detail using an indenter.
Keywords: characterization of polymers; π–π-interactions; self-healing polymers; supramolecular polymers